Seasonal Influenza Vaccination Uptake Among Australian Healthcare Professionals: An Archetype for Success - Caroline M. Hall; Anthony Cotton; Adrian Webster; Mary Bushell; Holly L. Northam (Vaccines)
Background/Objectives: Qualitative research suggests there may be identifiable characteristics that form a health professional (HCP) archetype associated with habitual seasonal influenza vaccination (SIV). However, the validity of this archetype requires further investigation, ideally within a theoretical framework that can elucidate this association and its generalisability to other vaccines. This study aims to confirm key HCP archetype characteristics associated with SIV, as informed by prior qualitative research findings, and test the generalisability of the association between this archetype and SIV to COVID-19 vaccine acceptance. Method: A cross-sectional survey was designed and distributed to an Australian HCP sample consisting of practicing nurses, midwives, pharmacists, and medical practitioners. The anonymous online survey measured key characteristics that predict vaccination behaviour and intention. Results: Most participants (n = 173) demonstrated habitual SIV behaviour (77.91%) associated with the intention to vaccinate in the future. Survey findings supported the HCP archetype, as key constructs were associated with vaccination intention and behaviour, including heightened professional responsibility, vaccine confidence, and protection of self and patients. Furthermore, results suggested progressing vaccination intention to behaviour, overcoming vaccine complacency, is possible through the provision of free, accessible vaccination services. These critical factors were broadly generalisable to the COVID-19 vaccine. Conclusions: A vaccination-positive HCP archetype, supported by access to free, convenient vaccination services, was associated with the likelihood of future vaccination behaviour, including in future pandemic response scenarios. However, it will be important to ensure that HCP vaccine knowledge gaps are minimised to enhance trust in this cohort to enable broad success.